2011
DOI: 10.1111/j.1095-8649.2011.03053.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and physiological responses of brook trout Salvelinus fontinalis to midwinter flow reduction in a small ice-free mountain stream

Abstract: This study presents an experimental analysis of the effects of midwinter flow reduction (50-75%, reduction in discharge in 4 h daily pulses) on the physical habitat and on behaviour and physiology of overwintering brook trout Salvelinus fontinalis in a small mountain stream. Flow reduction did not result in significant lowering of temperature or formation of surface or subsurface ice. The main findings were (1) daily movement by S. fontinalis increased (c. 2·5-fold) during flow reduction, but was limited to sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 56 publications
2
33
0
Order By: Relevance
“…A potential increase in evapotranspiration due to an increase in air temperatures in the region over the past decades may have also contributed to the decline in discharge (Schindler and Donahue 2006). Decrease in discharge can affect the availability and distribution of suitable fish habitat in streams (e.g., Krimmer et al 2011), which may indirectly affect fish through changes in the thermal regime, water chemistry, and decreases in invertebrate drift (Dewson et al 2007). …”
Section: Watersheds In Region: Hydrology Precipitation and Water Chmentioning
confidence: 99%
“…A potential increase in evapotranspiration due to an increase in air temperatures in the region over the past decades may have also contributed to the decline in discharge (Schindler and Donahue 2006). Decrease in discharge can affect the availability and distribution of suitable fish habitat in streams (e.g., Krimmer et al 2011), which may indirectly affect fish through changes in the thermal regime, water chemistry, and decreases in invertebrate drift (Dewson et al 2007). …”
Section: Watersheds In Region: Hydrology Precipitation and Water Chmentioning
confidence: 99%
“…In cases where the stressor persists over time, deleterious effects on overall fish performance (escaping predators, finding refuge, and foraging) and in specific life‐cycle stages (reproduction and growth) will likely occur (Barton, ; Pankhurst, ). Although changes in the blood physiology have occurred in down‐ramping conditions (Arnekleiv, Urke, Kristensen, Halleraker, & Flodmark, ; Flodmark et al, ; Krimmer et al, ), the flow conditions which trigger the stress response and the extent to which their severity may cause long‐term deleterious effects remain unknown. Studies conducted in the field or in laboratory conditions assert that the absence of a physiological response after a severe flow component fluctuation indicates that fish were seeking out velocity refuges (i.e., flow refuging), although this possibility has not been properly assessed (Arnekleiv et al, ; Flodmark et al, ; Taylor et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid fluctuations in water flow can also affect temporal aspects of stream fishes behaviour, for example, small and large-scale movements, relocation, and habitat use (Korman & Campana, 2009;Krimmer, Paul, Hontela, & Rasmussen, 2011;Riley, Maxwell, Pawson, & Ives, 2009;Scruton et al, 2005;Taylor et al, 2014). Other studies have suggested that salmonids also alter their diel feeding activity in response to hydropeaking (e.g., Rocaspana, Aparicio, Vinyoles, & Palau, 2016).…”
mentioning
confidence: 99%